2016
DOI: 10.1038/srep34125
|View full text |Cite
|
Sign up to set email alerts
|

JMJD8 is a positive regulator of TNF-induced NF-κB signaling

Abstract: TNF-induced signaling mediates pleiotropic biological consequences including inflammation, immunity, cell proliferation and apoptosis. Misregulation of TNF signaling has been attributed as a major cause of chronic inflammatory diseases and cancer. Jumonji domain-containing protein 8 (JMJD8) belongs to the JmjC family. However, only part of the family members has been described as hydroxylase enzymes that function as histone demethylases. Here, we report that JMJD8 positively regulates TNF-induced NF-κB signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Jmjd8 belongs to the family of JmjC domain-redox enzymes that catalyze protein hydroxylation or demethylation [32], as a role of Jmjd8 in regulating cellular metabolism and angiogenesis has been recently reported [33]. An oncogenic role of Jmjd8 as a positive regulator of TNF-induced NF-κB signaling in colorectal cancer has been described [34,35]; however, a recent study demonstrated that JMJD8 knockdown promotes cell proliferation and double-strand base (DSB) repair in lung and bone cancer cells, suggesting that Jmjd8 could represent a potential target for more effective tumor radio-and chemotherapies [36]. As a member of Wnt/β-catenin family, an oncogenic role for Wnt3 has been reported in different cancer types, including colorectal, gastric, breast, liver, and lung cancer [37][38][39][40][41]; yet a potential tumor-suppressor role for Wnt3 has been described in chronic lymphocytic leukemia, where decreased Wnt3 expression is associated with disease progression and worse prognosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Jmjd8 belongs to the family of JmjC domain-redox enzymes that catalyze protein hydroxylation or demethylation [32], as a role of Jmjd8 in regulating cellular metabolism and angiogenesis has been recently reported [33]. An oncogenic role of Jmjd8 as a positive regulator of TNF-induced NF-κB signaling in colorectal cancer has been described [34,35]; however, a recent study demonstrated that JMJD8 knockdown promotes cell proliferation and double-strand base (DSB) repair in lung and bone cancer cells, suggesting that Jmjd8 could represent a potential target for more effective tumor radio-and chemotherapies [36]. As a member of Wnt/β-catenin family, an oncogenic role for Wnt3 has been reported in different cancer types, including colorectal, gastric, breast, liver, and lung cancer [37][38][39][40][41]; yet a potential tumor-suppressor role for Wnt3 has been described in chronic lymphocytic leukemia, where decreased Wnt3 expression is associated with disease progression and worse prognosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we showed that JMJD8 functions as a positive regulator of the TNF-induced NF-κB pathway 16 . To better understand the biological functions of JMJD8, we sought to identify the interacting partners of JMJD8.…”
Section: Resultsmentioning
confidence: 99%
“…revealed that JMJD8 localizes to the extranuclear region instead of the nucleus. Interestingly, we previously demonstrated that JMJD8 is a positive regulator of the TNF signaling pathway 16 . In addition, ubiquitinated NF-κB signaling components, including RIP1, Bcl10 and TRAF2, have been shown to be recruited to the ER, which is required for optimal activation of NF-κB 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, JMJD8 has been shown to positively regulate TNF induced NF-κB signalling, although the mechanism by which this occurs has not been elucidated [102]. These reports further highlight some known and potential crosstalk points between hypoxia and NF-κB.…”
Section: Jmjcsmentioning
confidence: 97%